Bolstering Corporate Sector Partnership in the Fight against Financial Crimes in the Developing World: The Experience of West Africa - Shehu, Abdullahi Y (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Financial crime threatens the credibility and efficiency of systems and the stability of countries. Countering it requires concerted and collaborative efforts and strategic partnership between the public and private sectors. This paper discusses the roles of the private sector and challenges of compliance with acceptable international standards against money laundering and terrorist financing. The paper suggests that most of challenges, especially with regard to the reporting of suspicious transactions have almost been overcome, yet, there other challenges that remain. It concludes by making recommendations to address those challenges and improving the efficiency of the financial system.